2006
DOI: 10.1245/s10434-006-9180-z
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Guided Fine Needle Aspiration with Rapid Parathyroid Hormone Assay

Abstract: The use of rapid PTH assay can be effectively utilized for localization of parathyroid tissue in remedial parathyroid surgery. Confirmation of localization markedly improves subsequent surgery and allows selective use of minimally invasive techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 10 publications
5
60
1
1
Order By: Relevance
“…No adverse events were reported in our study or in that of Erbil et al(2006;. Maser et al(2006), who made 2~9 passes, reported 1 in situ infection, while Abraham et al(2007) reported 1 syncope and Marcocci et al(1998) 1 local haemorrhage. So far, more than 12 months after successful surgery, no recurrence of hyperparathyroidism as an expression of FNAB parathyromatosis has been noted in our series of patients; similar results were reported by Marcocci et al(1998).…”
Section: Resultsmentioning
confidence: 43%
See 3 more Smart Citations
“…No adverse events were reported in our study or in that of Erbil et al(2006;. Maser et al(2006), who made 2~9 passes, reported 1 in situ infection, while Abraham et al(2007) reported 1 syncope and Marcocci et al(1998) 1 local haemorrhage. So far, more than 12 months after successful surgery, no recurrence of hyperparathyroidism as an expression of FNAB parathyromatosis has been noted in our series of patients; similar results were reported by Marcocci et al(1998).…”
Section: Resultsmentioning
confidence: 43%
“…An intra-operative PTH-FNAB value >1000 ng/L has been reported in 88% of patients with parathyroid adenoma. Maser et al(2006) reported that a PTH-FNAB value >1000 ng/L unequivocally indicates sampling in parathyroid tissue. In our series, only 38% of patients showed PTH-FNAB values >1000 ng/L.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is possible to determine PTH in the material aspirated by means of FNAB. The published reports on this method are encouraging so far [6,8,9,[15][16][17][18][19][20][21][22][23][24][25]. But only in a few studies has the influence of co-existing nodular goitre on the discussed method been analysed [6,8,24].…”
Section: Introductionmentioning
confidence: 99%